PID_(n-2)/2 Stage PDA Cascade Robust Controllers - Kitti Tirasesth; Jongkol Ngamwiwit; Thanit Trisuwannawat; Noriyuki Komine; Yasuzumi Ochiai (My University, 2000)
This paper presents a design technique for the two-degree of freedom control system using PID×(n-2)/2 stage PDA as a cascade robust controller for a class of nth order plants. It is intended to satisfy both transient and steady state response specifications based on root locus approach. This controller can be used instead of a conventional PID controller for the higher order plant to obtain better performances. By this design technique, the controlled system is approximated as a second order system, and the desired performances are satisfied. For the plant with stable poles including the case with small dead time, the closed-loop poles are located on the left half of the s-plane and the controlled system become robustly stable. The cascade robust controller gain is adjusted to meet faster responses with a small or no overshoot. Robustness properties given by the controllers proposed in this paper have also been demonstrated by illustrative examples.
Keywords: Robustness; Root locus; Overshoot (microwave communication); Advanced Control Systems Design